The Progressive Republican Party of 1924-25: Reactionaries, Conservatives, or Moderates? - Erik-Jan Zürcher (European Journal of Turkish Studies)
This article tries to make sense of the ideological position of the Progressive Republican Party of 1924-5. It does so by making two separate points.Firstly, it argues that, under the influence of the politics of the French Third Republic, the early Kemalists, like the Unionists before them, had a strong inclination to see all those who opposed their own revolutionary radicalism as reactionaries rather than as conservatives. Because conservatism was defined as reaction-in-disguise it could not gain legitimacy as a political current. The historiographical tradition based on the dichotomy of radical/reactionary that the Kemalists established during the single-party period had a long-lasting effect in the way the PRP was viewed. Secondly, the article asks the question what is the result if we free ourselves from the Kemalist view of the PRP as reactionary (or enabling reactionaries) and try to determine whether the party was in fact truly conservative. On the basis of the party’s own programme, the conclusion is that it is quite far removed from philosophical conservatism and can be better characterised as the moderate and liberal wing of the same radical current the Kemalists themselves formed part of.